A combined impedance and traveling wave based fault location method for multi-terminal transmission lines - Ngu, E.E.; Ramar, K. (ELSEVIER SCI LTD, 2011)
A new fault location method suitable for multi-terminal transmission lines that combines the advantages of both impedance and traveling wave based methods has been developed and presented in this paper. The proposed method first determines whether the fault is grounded or ungrounded by comparing the magnitude of the ground mode wavelet coefficients at the measurement end. Next, the impedance based method is used to identify the faulted half of the line in the case of two-terminal line and the faulted line section as well as the faulted half of the line section in the case of multi-terminal lines. Finally the fault location is determined by taking the time difference between the first two consecutive aerial modes of the current traveling waves observed at one end of the multi-terminal line. The proposed method has been tested on four- and five-terminal transmission lines with different types of faults, fault resistances and fault inception angles using ATP simulation. (C) 2011 Elsevier Ltd. All rights reserved.